Safety and Security Co-Design in Automotive Semiconductor Systems: Challenges and Future Directions - Sujan Hiregundagal Gopal Rao (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As vehicles grow more connected and automated, semiconductors inside ECUs are the linchpin of both safety and security. Historically treated separately, safety (ISO 26262) and cybersecurity (ISO/SAE 21434) must now be co-designed so that security measures do not inadvertently compromise timing-critical safety behavior and safety mechanisms do not introduce new vulnerabilities. This paper surveys recent work on safety–security co-design at the semiconductor and ECU level, synthesizes practical challenges, and proposes directions for research and industry practice. Three conceptual figures and two summary tables are embedded at contextually appropriate points in the manuscript to aid comprehension. Key recent studies and industry reports are cited to ground recommendations. <!–StartFragment –>DOI: https://doi.org/10.17762/ijisae.v12i4s.7999<!–EndFragment –>